The Structural Equation Model of causal factor influencing attitudes for using self-checkout machine in modern trade in Bangkok - Taweesuk, Prerapha (Journal of Humanities and Social Sciences Thonburi University, 2022)
The purposes of this research were to study 1) Develop the model of perception of technology acceptance and attitude toward using self-checkout machines (SCM), 2) Examine the coherence of the technology adoption model and shoppers’ attitudes towards use of SCM with empirical data and 3) To study the causal factors between technology acceptance and SCM in modern trade in Bangkok. Questionnaire was used a research tool, 450 samples of consumers SCM were collected. The path analysis was used to test the hypotheses. The Structural equation modeling: SEM was used to test the causal factors between technology acceptance and attitudes toward using SCM in modern trade in Bangkok. The results showed the causal relationship of the SEM was created consistently with the empirical data and had the ability to predict at a good level and at the level of acceptance of 64 percent. According to the causal relationship were found innovation factors, perceived stimulus, perceived ease of use directly and indirectly effect related through perceived usefulness. For the subjective norm factor, there were an indirect effect through perceived ease use and perceived usefulness. Finally, was found the direct effect of the perceived usefulness factor and the attitude of SCM among shoppers in modern trade in Bangkok at the statistically significant level 0.05.